Analyzing Consumer Shopping Interest Drivers: The Impact of Promotional Strategies in E-Commerce Among Muslim Students - Hakim, Miftahur Rahman; Kadir, Afifuddin; Indi, Anita; Adel, Adel (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2024)
This study investigates how key promotional strategies influence online shopping interest among Muslim university students, focusing specifically on discounts, free shipping offers, and cash-on-delivery (COD) payment systems in the Shopee e-commerce platform. Using a quantitative approach with survey data from 100 Muslim students in Kendari City selected through quota sampling, and the research employs ordinal regression analysis to examine the relationships between these promotional elements and shopping interest. The findings reveal that discounts and free shipping offers significantly influence shopping interest, with discount promotions showing the strongest effect (odds ratio of 2.19), followed by free shipping (odds ratio of 1.29). Interestingly, the COD payment system demonstrates no significant impact on shopping interest. The model explains 52.3% of the variance in shopping interest, highlighting the substantial role of promotional strategies in driving e-commerce adoption among Muslim students. These results provide valuable insights for e-commerce platforms and marketers in developing targeted promotional strategies for the Muslim student segment. The study contributes to the understanding of Muslim consumer behaviour in digital commerce by demonstrating how different promotional tools influence their shopping interests while considering their unique characteristics as digital-native consumers with specific religious values and limited disposable income.